Born a crime and other stories - Noah, Trevor 1984- (John Murray, 2017)
As host of the US hit show The Daily Show, Trevor Noah provides viewers around the globe with their nightly dose of biting satire, but here Noah turns his focus inward, giving readers a deeply personal, heartfelt and humorous look at the world that shaped him. Noah was born a crime, son of a white Swiss father and a black Xhosa mother, at a time when such a union was punishable by five years in prison. Living proof of his parents' indiscretion, Trevor was kept mostly indoors for the first years of his life, bound by the extreme and often absurd measures his mother took to hide him from a government that could, at any moment, take him away. A collection of eighteen personal stories, BORN A CRIME tells the story of a mischievous young boy growing into a restless young man as he struggles to find his place in a world where he was never supposed to exist. BORN A CRIME is equally the story of that young man's fearless, rebellious and fervently religious mother - a woman determined to save her son from the cycle of poverty, violence and abuse that ultimately threatens her own life
Originally published: London : John Murray, 2016
Keywords: Noah, Trevor / 1984-; Noah, Trevor / 1984- / Childhood and youth; Comedians / United States / Biography; Comedians / South Africa / Biography; Television personalities / United States / Biography; Apartheid / South Africa; Mothers and sons / South Africa; South Africa / History / 1961-1994; South Africa / History / 1994-; South Africa / Social conditions / 1961-1994; South Africa / Social conditions / 1994-; Autobiographies; Fiktionale Darstellung; Autobiografie